Angiotensinogen and Megalin Interactions Contribute to Atherosclerosis—Brief Report. Issue 2 (February 2019) - Ye, Feiming; Wang, Ya; Wu, Congqing; Howatt, Deborah A.; Wu, Chia-Hua; Balakrishnan, Anju; Mullick, Adam E.; Graham, Mark J.; Danser, A.H. Jan; Wang, Jian'an; Daugherty, Alan; Lu, Hong S.
Abstract : Objective—: AGT (Angiotensinogen) is the unique precursor of the renin-angiotensin system that is sequentially cleaved by renin and ACE (angiotensin-converting enzyme) to produce Ang II (angiotensin II). In this study, we determined how these renin-angiotensin components interact with megalin in kidney to promote atherosclerosis. Approach and Results—: AGT, renin, ACE, and megalin were present in the renal proximal convoluted tubules of wild-type mice. Hepatocyte-specific AGT deficiency abolished AGT protein accumulation in proximal tubules and diminished Ang II concentrations in kidney, while renin was increased. Megalin was most abundant in kidney and exclusively present on the apical side of proximal tubules. Inhibition of megalin by antisense oligonucleotides (ASOs) led to ablation of AGT and renin proteins in proximal tubules, while leading to striking increases of urine AGT and renin concentrations, and 70% reduction of renal Ang II concentrations. However, plasma Ang II concentrations were unaffected. To determine whether AGT and megalin interaction contributes to atherosclerosis, we used both male and female low-density lipoprotein receptor −/− mice fed a saturated fat-enriched diet and administered vehicles (PBS or control ASO) or megalin ASO. Inhibition of megalin did not affect plasma cholesterol concentrations, but profoundly reduced atherosclerotic lesion size in both male and female mice. Conclusions—: These results reveal a regulatory role of megalin in the intrarenal renin-angiotensin homeostasis and atherogenesis, positing renal Ang II to be an important contributor to atherosclerosis that is mediated through AGT and megalin interactions. Abstract : Supplemental Digital Content is available in the text.